Woody plant encroachment into grasslands leads to accelerated erosion of previously stable organic carbon from dryland soils. Issue 12 (30th December 2014) - Puttock, Alan; Dungait, Jennifer A. J.; Macleod, Christopher J. A.; Bol, Roland; Brazier, Richard E.
Abstract Drylands worldwide are experiencing rapid and extensive environmental change, concomitant with the encroachment of woody vegetation into grasslands. Woody encroachment leads to changes in both the structure and function of dryland ecosystems and has been shown to result in accelerated soil erosion and loss of soil nutrients. Covering 40% of the terrestrial land surface, dryland environments are of global importance, both as a habitat and a soil carbon store. Relationships between environmental change, soil erosion, and the carbon cycle are uncertain. There is a clear need to further our understanding of dryland vegetation change and impacts on carbon dynamics. Here two grass‐to‐woody ecotones that occur across large areas of the southwestern United States are investigated. This study takes a multidisciplinary approach, combining ecohydrological monitoring of structure and function and a dual‐proxy biogeochemical tracing approach using the unique natural biochemical signatures of the vegetation. Results show that following woody encroachment, not only do these drylands lose significantly more soil and organic carbon via erosion but that this includes significant amounts of legacy organic carbon which would previously have been stable under grass cover. Results suggest that these dryland soils may not act as a stable organic carbon pool, following encroachment and that accelerated erosion of carbon, driven by vegetation change, has important implications for carbon dynamics.